ANALISIS TINGKAT KESEJAHTERAAN TENAGA KERJA BONGKAR MUAT (TKBM) DI PELABUHAN CIREBON - Susilawati; Fereddy Siagian; Willem Nikson.S. (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
Article History Received: Revised: Published: Keywords: Welfare Level, TKBM, Cirebon Port Abstract: This research aims to analyze the welfare level of loading and unloading workers (TKBM) at Cirebon Port. This research uses an observational survey method approach to related parties and a sample of TKBM at Cirebon Port. The scope of discussion includes income, working hours, social security and work environment. The aim of the research is expected to improve the welfare of TKBM in carrying out loading and unloading tasks at the Port of Cirebon. The research methodology uses the analytical method approach Descriptive Analysis, Welfare Analysis, Comparative Analysis, Qualitative Analysis through the qualitative research approach model Spradley Sugijono, 2009:345, namely domain analysis, taxonomy, componential and cultural themes. The research results show that in general, the welfare level of TKBM at Cirebon Port is still relatively low. TKBM's average income is only IDR 2,500,000 per month, with working hours reaching 10 hours per day. Only a small number of TKBM have social security such as BPJS Employment and BPJS Health. Apart from that, inadequate working conditions, such as limited rest facilities, are also a problem. The Cirebon Port management needs to improve the welfare of TKBM through increasing income, providing adequate social security, and improving the work environment. KataKunci: Tingkat Kesejahteraa,TKBM, Pelabuhan Cirebon Abstrak: Penelitian ini bertujuan untuk menganalisis tingkat kesejahteraan tenaga kerja bongkar muat (TKBM) di Pelabuhan Cirebon. Penelitian ini menggunakan pendekatan metode survey observasi, kepada pihak terkait dan sampel para TKBM di Pelabuhan Cirebon. Ruang lingkup bahasan meliputi pendapatan, jam kerja, jaminan sosial, dan lingkungan kerja. Tujuan penelitian diharapkan dapat meningkatkan kesejahteraan TKBM dalam menjalankan tugas-tugas bongkar muat di Pelabuhan Cirebon. Metodologi penelitian menggunakan pendekatan metode analisis Analisis Deskriptif, Analisis Kesejahteraan, Analisis Komparatif, Analisis Kualitatif melalui pendekatan penelitian kualitatip model Spradley Sugijono, 2009:345 yaitu analisis domain, taksonomi, komponensial dan tema cultural. Hasil penelitian menunjukkan bahwa secara umum, tingkat kesejahteraan TKBM di Pelabuhan Cirebon masih tergolong rendah. Pendapatan rata-rata TKBM hanya Rp 2.500.000 per bulan, dengan jam kerja mencapai 10 jam per hari. Hanya sebagian kecil TKBM yang memiliki jaminan sosial seperti BPJS Ketenagakerjaan dan BPJS Kesehatan. Selain itu, kondisi lingkungan kerja yang kurang memadai, seperti fasilitas istirahat yang terbatas, juga menjadi masalah. Pihak pengelola Pelabuhan Cirebon perlu meningkatkan kesejahteraan TKBM melalui peningkatan pendapatan, penyediaan jaminan sosial yang memadai, serta perbaikan lingkungan kerja.